In silico screening and prediction of allergenicity of oriental mole cricket Gryllotalpa orientalis - Sanchez, John Rinno B. (College of Home Economics, University of the Philippines Diliman, 2023)
Consumption of edible insects presents a possible solution to increasing global food security issues as an alternative food source due to various nutritional benefits such as higher feed conversion efficiency compared to livestock. However, there are limited studies on the allergenicity of local species of edible insects. This study uses an in silico approach to predict for allergenicity of the oriental mole cricket Gryllotalpa orientalis. Further assessment is also done to predict for reduction of allergenicity via simulated gastrointestinal peptide digestion using in silico tools. Collected protein sequences from Uniprot were screened for possible allergenicity using the hybrid method of AlgPred 2.0. Six out of twenty-nine sequences were predicted to be allergens (Superoxide dismutase [Cu-Zn] (EC 1.15.1.1), polyprotein, myosin light chain, peroxiredoxin, glutathione s-transferase, chemosensory protein). Further analysis with Allermatch and Allfam determined high similarity of the proteins with known allergenic proteins found in species such as Olea europea, Periplaneta americana, Blatella germanica, Triticum aestivum, and Thaumetopoea pityocampa, indicating a possibility for cross reactivity. Identified IgE epitopes of the protein sequences exhibited resistance to simulated gastrointestinal peptide digestion using the enzymes pepsin (pH = 1.2, 2.0), trypsin, and chymotrypsin (high and low sensitivity). In silico analysis of G. orientalis proteins indicate a possibility of allergenicity according to FAO/WHO guidelines.